Analisis Faktor Risiko Kejadian Hipertensi pada Pra Lansia dan Lansia di Kelurahan Kedaung Kota Depok: Analysis of Risk Factors Contributing to Hypertension in Pre-Elderly and Elderly Populations in the Kedaung Subdistrict, Depok, Indonesia - Wirayudha, Gibran; Ilmi, Ibnu Malkan Bakhrul; Marjan, Avliya Quratul (Amerta Nutrition, 2024)
Background: West Java Province ranks third in Indonesia's highest incidence of hypertension. According to Depok City Health Office data, 3,283 individuals aged ≥15 years in the Kedaung Subdistrict suffer from hypertension, highlighting multifactorial causes beyond aging. Objectives: To identify the primary risk factors for hypertension in pre-elderly and elderly individuals in the Kedaung Subdistrict. Methods: The study utilized a cross-sectional design involving pre-elderly and elderly individuals from the Kedaung Subdistrict. The research sample comprised 50 participants selected using stratified random sampling techniques. Data collection was conducted through a structured questionnaire. Univariate analysis was performed using frequency distribution, bivariate analysis using chi-square tests, and multivariate analysis using a logistic regression test. Results: Nutritional status (p-value=0.028) and sodium intake (p-value=0.016) were significantly associated with hypertension among pre-elderly and elderly individuals in the Kedaung Subdistrict. Conversely, family history (p-value=0.615) and smoking habits (p-value=0.459) showed no significant association with hypertension. Conclusions: Sodium (sodium) intake was identified as a significant risk factor for hypertension among pre-elderly and elderly individuals in the Kedaung Subdistrict. Individuals with excessive sodium intake have a higher likelihood of developing hypertension compared to those with lower sodium consumption.  Pre-elderly and elderly populations are advised to monitor and regulate their sodium intake to reduce the risk of hypertension.